System performance and detectable faults of a 10-year old 1.1 kWp GCPV system in Malaysia / Nurmalessa Muhammad ... [et al.]. - Muhammad, Nurmalessa; Zakaria, Nor Zaini; Shaari, Sulaiman; Omar, Ahmad Maliki (2017)
This paper presents the findings of a study conducted to evaluate the performance and to identify faults of a 10-year old 1.1kW grid-connected photovoltaic (GCPV) system installed at Green Energy Research Center (GERC), Universiti Teknologi MARA (UiTM), Shah Alam. The system performance was evaluated by comparing the real operating field data with the data declared by the manufacturer. Eight performance indicators were used, which are: reference yield, array yield, final yield, capture losses, system losses, performance ratio, PV array efficiency and total efficiency. The fault detection has used three techniques - which were visual inspection as outlined in the International Energy Agency (IEA) document, thermal imager technique and the I-V curve characteristics. The finding for the system performance evaluation gives a 13.2% difference between the real operating field data and the declared manufacturer data. Among the faults detected from the visual inspection are browning and cracks of PV modules.